Surface trace gases during METEOR cruise M157 - Bita Sabbaghzadeh; Michael Glockzin; Gregor Rehder (PANGAEA, 2022)
The high surface productivity triggered by nutrient-rich Benguela upwelled waters results in significant enrichment of organic carbon in the sub-surface waters due to enhanced mineralization in the water column and benthic fluxes. Hence, microbial O2-consuming processes are promoted, driving oxygen depletion that favors trace gases i.e. methane (CH4) and nitrous oxide (N2O) production at relatively shallow depths. During upwelling, gas-rich subsurface waters are also transported towards the surface waters, enhancing trace gas sea-air fluxes. We investigate the variability of these fluxes on seasonal and shorter timescales to understand the intensity of the Benguela upwelling system in gas emissions. The data might serve as a base for projections under a changing climate. The fieldwork took place during the cruise M157 (August 4th – September 16th, 2019) onboard the R/V METEOR, which encompassed close-coastal and open ocean regions between Mindelo (Cape Verde) and Walvis Bay. The main transect lines around 18, 23 and 25°S represents the Angola-Benguela frontal zone, Walvis Bay and Lüderitz upwelling cells respectively, which are suggested to represent some regional hotspots of trace gas emissions to the atmosphere, in particular in the vicinity of the upwelling cells. The partial pressures of CH4, N2O, and CO2 as well as oxygen saturation in surface water were determined using IOW extquotesingles self-built Mobile Equilibrator Sensor System (MESS). The system was described in details elsewhere (Sabbaghzadeh et al., 2021) but in brief, it consists of a custom-built equilibrator (combined shower-head/bubble type) with a water flow rate of about 5 l min-1 and an airflow rate of ~ 4 l min-1, which is linked to two off-axis integrated cavity output laser spectrometers (oa-ICOS, Los Gatos Instruments) for the detection of CH4 / CO2 and N2O / CO. Seawater was supplied by a pump installed at a water depth of about 6 m in the moon pool on board of RV METEOR. oa-ICOS sensors combine a highly specific infrared band laser with a set of reflective mirrors and achieve an effective absorption path length of several kilometers. This enables the detection of the trace gases with high accuracy. Three standard gases, provided by the central calibration lab of the European Integrated Carbon Observation System Research Infrastructure (ICOS RI) were used to calibrate the sensors almost daily throughout the entire expedition. To estimate sea-air gas fluxes, the atmospheric concentration of trace gases was also measured at several positions during the cruise using a tube with the inlet positioned to minimize ship contamination. All other ancillary parameters out of the MESS system were synchronized with D-ship data with a simultaneous data reduction to one-minute intervals.